2014
DOI: 10.4028/www.scientific.net/amr.891-892.955
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Lifetime and Crack Growth Behavior of WC-Co Cemented Carbide

Abstract: It is well known that WC-Co cemented carbides have excellent wear resistance. However, information about their fatigue crack growth behavior and fatigue properties is limited. In the present study, rotating bending fatigue tests were carried out on a fine grained WC-Co cemented carbide to evaluate its fatigue lifetime and crack growth behavior. From observations of the micro-notched specimen surface during the fatigue process, it was revealed that most of the fatigue lifetime of the tested WC-Co cemented carbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Therefore, a value of 0.73 was used for Y, as used in Equation (1). From the fracture surface observations, it was confirmed that the fatigue crack initiation site for the present material was an aggregate of several WC grains or a coarse WC grain slightly beneath the specimen surface [21].…”
Section: Observation Of the Crack Growth Pathmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, a value of 0.73 was used for Y, as used in Equation (1). From the fracture surface observations, it was confirmed that the fatigue crack initiation site for the present material was an aggregate of several WC grains or a coarse WC grain slightly beneath the specimen surface [21].…”
Section: Observation Of the Crack Growth Pathmentioning
confidence: 99%
“…In the present study, the maximum stress intensity factor, Kmax, was utilized, as in previous studies [4,21]. To calculate the Kmax, the following expression was used:…”
Section: Experimental Procedures For Fatigue Testsmentioning
confidence: 99%
See 1 more Smart Citation